Africans in China and Chinese in Africa: inequalities, social identities, and wellbeing. Issue 4 (1st October 2020) - Amoah, Padmore Adusei; Hodzi, Obert; Castillo, Roberto
ABSTRACT: Relations between China and African nations have intensified following the ratification of several multilateral and bilateral developmental agreements, especially after the third Forum on China-Africa Cooperation (FOCAC) summit in 2006. In the past decade, the relations have transcended to the micro-level, with important implications for households and individuals. Of note are the varying forms of population migration between the two places for reasons ranging from business ventures, education, asylum-seeking and family making and reunification. Using various primary and secondary data sources, the seven articles in this special issue delve into the wellbeing, social identities and different kinds of socio-cultural and economic inequalities of Africans in China and Chinese in Africa. Altogether, the articles affirm that policies and mechanisms to ensure decent living conditions, enhanced sense of belonging and social equity among Africans in China and Chinese in Africa are critical to the future of China-Africa relations.